Shredded tire as partial aggregate replacement in producing high flexural beam - Rainita, Adin (2014)
Nowadays, sustainable construction had gain wide attention in the engineering community. There are some standards developed to asses any environment impact of new construction projects. Refer to the research and study shown that is possible to use recycled materials to replace some material in concrete product. Rubber tire particles are recycled and currently use in concrete application. This study determines the use of rubber tire particles as partial coarse aggregate replacement for the mixture design of the concrete. There are three hollow section beams with different cavity sizes as specimens for this study to determine the effect of cavity sizes to the hollow section beam. There are three different cavity sizes for hollow section beam, 40mmxlOOmm, 50mmxlOOmm and óOmmxlOOmm. The process included of filling the concrete in the solid and hollow beam section formwork. The materials then undergo consolidation process. Then the sample are removed three day after from the formwork and transferred to the curing process. The beams cure for 28 days. The beam made with the rubber tire particles were testing for its flexural strength. The result showed that hollow section beam with cavity size 60mmxlOOmm had the higher flexural strength compare with all specimens. In conclusion, the bigger the cavity sizes for the hollow section beams, the higher the load-deflection ratio for the beam. Thus, the bigger the cavity sizes, the higher the flexural strength of the beam.